Productive performance, metabolic, and hematologic parameters of pregnant nulliparous rabbit does according to dietary protein level - Saidj, Dahia; Ainbaziz, Hacina; Iles, Imene; Dahmani, Yamina; Hornick, Jean Luc; Moula, Nassim (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aims at investigating the productive performance, metabolic, and hematological profiles of Algerian local rabbits does during their first pregnancy and according to dietary protein content. Materials and methods: A total of 52 nulliparous rabbit does, 3,116 ± 72.9 g live weight, were allocated individually to three groups (17/18 females per group) being on isoenergetic diets [2,600 kcal Digestible Energy (DE)/kg] that differ in their digestible protein content by 15%, 17%, and 19%, respectively, for L, M, and H diets. All these diets were provided ad libitum. Results: The use of a high protein diet did not affect does weight and feed intake during the pregnancy period. Statistically, no significant difference (p > 0.05) was recorded in born or alive litter size and birth weight. There was no effect of diet and sampling time (p > 0.05) on plasma metabolites but there were significant effects of sampling time (p < 0.0001) on the metabolic parameters studied with prolificacy used as a covariate. Hematologic indices in pregnant rabbits were not affected by the diet exceeded the red blood cells rate that increased significantly (p < 0.05) with the increase in dietary protein content during the different periods of gestation. Conclusion: The use of a high protein diet has no effect on weight during the pregnancy period. No effect of diet and sampling time on plasma metabolites and hematological profiles are recorded; however, significant effects of sampling time are recorded on the metabolic parameters. J. Adv. Vet. Anim. Res., 6(1): 18-24, March 2019